(untitled) (Sustainability in Debate, 2021)
In coastal Ecuador pre-Columbian rainwater management systems are still in use, allowing the social reproduction of native societies. However, such successful and traditional technology is being replaced in public policies by small dams and detention ponds which in the local social imaginary represent modernity and progress. While traditional Albarradas are the ones successful in achieving environmental sustainability in the region, thanks to communal cultural patterns associated with them. To separate the concept of sustainable it is necessary to discuss the transformation the developmental cultural matrix for a change in ethics in our relations with nature as a common property of public use.